Fiqih dan Prinsip Ibadah dalam Islam - Khaeru Nazwa; Bunga Khansa Tikwana; Safira, Adria; Andriyani Andriyani; Wahdi Sayuti; Raghib Filhaq (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study discusses fiqh ibadah as an important branch of fiqh that regulates the procedures for performing worship in accordance with Islamic law. The main objective of this study is to clarify the basic concepts of law, principles, and scope of worship in Islam so that its implementation is in accordance with sharia provisions. The data sources consist of primary literature (the Qur'an and Hadith) by analyzing scientific works from Google Scholar from 2018 to 2025 sourced from Indonesian and English journals. This study systematically describes the meaning of fiqh ibadah, sharia, and the legal basis derived from the Qur'an, sunnah, ijma, and qiyas. It includes complete arguments such as istihsan, maslahah, and urf. The discussion also covers the principles of ibadah mahdhah, which emphasize the necessity of evidence in its implementation to prevent bid'ah practices. The scope of fiqh ibadah focuses on four main acts of worship, namely prayer, zakat, fasting, and hajj, which have specific provisions in sharia. In addition, it also discusses the essence and purpose of worship, which shows that worship is a form of submission and love of a servant to Allah SWT and the main purpose of human creation. Through an understanding of fiqh worship, Muslims are expected to be able to perform worship correctly, validly, and accepted by Allah SWT, as well as a means of achieving benefit and happiness in this world and the hereafter.